The Impact of Good Governance, Employee Competence, and Accounting Information Systems on Financial Report Quality in The Bandung City Government - Edo William Nemnay; R. Ait Novatiani (Universitas Kristen Maranatha, 2026)
Purpose – This study was conducted to empirically investigate the extent to which the implementation of good governance, human resource capabilities, and the functionality of accounting information systems affect the quality of financial reports within the Bandung City Government. Design/Methodology/Approach – This research applies a quantitative approach with a population coverage of 31 Regional Work Units (SKPD) within the Bandung City Government. The sample was determined using a non-probability sampling technique with a purposive sampling method, based on specific criteria: (1) employees in the finance and accounting functions who are authorized to make budget decisions and prepare regional financial reports, and (2) have a minimum of two years of service in the field. Based on these criteria, a sample of 39 employees was obtained who have relevant tasks and direct authority in the financial reporting process at the related work unit. Findings – The research findings confirm that all independent variables have a significant influence on the dependent variable. The integration of sound governance principles, employee professionalism, and accounting information system infrastructure support has proven to be crucial in producing accurate and transparent financial reporting for government agencies. Research limitations/Implications – Despite the limited sample size and short observation period, the results of this study provide strategic implications for the Bandung City Government to integrate accountability principles more comprehensively. The quality of the resulting financial reports has a direct impact on increasing public trust, improving bureaucratic operational efficiency, and strengthening sustainable regional governance. Keywords: Accounting Information Systems, Employee Competence, Good Governance, Quality of Financial Reports